Parâmetros erosividade da chuva e da enxurrada correlacionados com as perdas de solo de um solo Bruno Não-Cálcico Vértico em Sumé (PB) - Albuquerque, A. W.; Lombardi Neto, F.; Cataneo, A. [UNESP]; Srinivasan, V. S. (Sociedade Brasileira de Ciência do Solo, 1998)
Simple linear correlations among runoff and rainfall erosivity parameters and soil losses caused by erosivity rainfall in Haplargids were studied. Data related to 1986-1990 were obtained in the Experimental Station at Sumé-Brazil. The rainfall erosivity parameters were the following: a) total height of the rainfall (P) in mm; b) maximum intensity (In): I5; I10; I15; I20; I25; I30; I35; I40; I45; I50; I55; I60 and I120 minutes in mm h-1, respectively; c) total kinetic energy by the Wischmeier & Smith's and by the Wagner & Massambani's methods in MJ ha-1 (KE and KEW); d) kinetic energy of intensities higher than 10 mm h-1 (KE > 10 and KEW > 10) in MJ ha-1; e) kinetic energy of intensities higher than 25 mm h-1 (KE > 25 e KEW > 25) in MJ ha-1; f) total kinetic energy products by maximum intensities rainfall (EIn): EI5, EI10; EI15; EI20; EI25; EI30 EIW30; EI35; EI40; EI45; EI50; EI55; EI60 and EI120 in MJ mm ha-1h-1, respectively; g) total height of rainfall products by maximum intensity rainfall (PIn): PI5, PI10, PI15; PI20; PI25; PI30; PI35; PI40; PI45; PI50; PI55; PI60 and PI120 in mm² h-1, respectively; and h) runoff volume (Vu) in m³. The runoff erosivity parameter (Vu) best estimated (r = 0.812) the soil losses in Sumé-PB. Among rainfall erosivity parameters, the PI25 type (r = 0.753) was best correlated with soil losses. The Wischmeier & Smith's and the Wagner & Massambani's equations used to calculate the total kinetic energy rainfall presented the same degree of precision in estimating soil losses.

Foram estudadas correlações lineares simples entre os parâmetros erosividade da chuva e da enxurrada e as perdas de solo provocadas por chuvas erosivas num solo Bruno Não-Cálcico Vértico. Os dados correspondentes aos anos de 1986-1990 foram obtidos na estação experimental de Sumé (PB), pertencente à Universidade Federal da Paraíba-UFPB. Os parâmetros erosividade da chuva e da enxurrada estudados foram: (a) altura total da chuva (P), em mm; (b) intensidades máximas (In), ocorridas nos tempos de 5; 10; 15; 20; 25; 30; 35; 40; 45; 50; 55; 60 e 120 minutos, respectivamente, em mm h-1; (c) energia cinética total, pelo método de Wischmeier e Smith (Ec) e pelo método de Wagner e Massambani (EcW), em MJ ha-1; (d) somatório da energia cinética de intensidades superior a 10 mm h-1 (Ec > 10 e EcW > 10) em MJ ha-1; (e) somatório da energia cinética de intensidades superior a 25 mm h-1 (Ec > 25 e EcW > 25), em MJ ha-1; (f) produtos da energia cinética total pelas intensidades máximas de chuva em intervalos crescentes de tempo (EIn), ou seja: EI5; EI10; EI15; EI20; EI25; EI30; EIW30; EI35; EI40; EI45; EI50; EI55; EI60 e EI120, em MJ mm ha-1 h-1; (g) produtos da altura total da chuva pelas intensidades máximas das chuvas em intervalos crescentes de tempo (PIn), ou seja: PI5; PI10; PI15; PI20; PI25; PI30; PI35; PI40; PI45; PI50; PI55; PI60 e PI120, em mm² h-1, e (h) volume de enxurrada (Vu), em m³. O parâmetro volume de enxurrada (Vu) foi o que melhor estimou (r = 0,812) as perdas de solo em Sumé (PB). Dentre os parâmetros erosividade da chuva, o que melhor se correlacionou com as perdas de solo foi o parâmetro PI25 (r = 0,753). As equações de Wischmeier & Smith e de Wagner & Massambani, utilizadas no cálculo da energia cinética total da chuva, apresentaram o mesmo grau de precisão na estimativa das perdas de solo.
Rainfall and runoff erosivity parameters correlated with soil losses of a haplargids (Paraiba state, Brazil)
Keywords: erosividade; erosão; Bruno Não-Cálcico; erosion; rainfall erosivity parameter; runoff erosivity parameter; runoff-rainfall erosivity parameter